Public Perception of the Covid-19 Disease in The Wakorambu Village - Nuur Rahmatul Asma; Fikki Prasetya; Rizki Eka Sakti Octaviani Kohali (Universitas Mandala Waluya, 2021)
Coronavirus Disease (Covid-19) is a new type of disease that has never been identified before in humans. Public perception in Batalaiworu Subdistrict shows that most of them still lack concern for maintaining health protocols and lack of trust in the existence of Covid-19. This study aims to describe the public perception of the Covid-19 disease in the village of Wakorambu, Batalaiworu District, Muna Regency. This study uses quantitative research with a descriptive approach. The number of samples in this study were 76 respondents with the sampling technique of proportional stratified random sampling. The results showed that public knowledge of the Covid-19 disease was more in sufficient category (92.10%), perceived susceptibility to Covid-19 was more in sufficient category (84.21%), perceived severity against Covid-19 19 more enough categories (80.26%), perceived benefits for Covid-19 more enough categories (90.78%), perceived barriers to Covid-19 more poor categories (63, 15%), perception of threat to Covid-19 is more in sufficient category (69.73%), and cues to Action towards Covid-19 are more in sufficient category (72.36%). Conclusions based on the results of the study, it can be concluded that knowledge, perceived susceptibility, perceived severity, perceived benefits, perceived barriers, threats and cues to action indicate a perceived lack of barriers to Covid-19 disease in Wakorambu village in preventing Covid-19.